Reformulasi Pengelolaan Penyertaan dan Penatausahaan Modal Negara pada BUMN Berbentuk Perseroan Terbatas - Saputra, Ardi (Universitas Negeri Malang, 2022)
This study aimed to analyze the inconsistency of regulations related to the participation and administration of state capital in State-Owned Enterprises in the form of limited companies and the reformulation of regulations related to the participation and administration of state capital in State-Owned Enterprises with legal certainty and utility. The study applied a statutory approach and a conceptual approach. The type of research used was normative juridical research data sources obtained from primary, secondary and tertiary legal materials. The data analysis technique used a grammatical and systematic interpretation method. The study results showed that the inconsistency of the laws and regulations governing the mechanism for the participation and administration of state capital created overlaps and multiple interpretations. The management of State-Owned Enterprises was ineffective, inefficient, and lacked agility as a corporate entity. Reformulation of laws and regulations related to State-Owned Enterprises need to be carried out by classifying the role of State-Owned Enterprises for the Indonesian economy based on their role and deregulation of laws and regulations to create State-Owned Enterprises that were globally competitive.